THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH REWARD AND PUNISHMENT AS MODERATION VARIABLES (CASE STUDY : PT SALIM IVOMAS PRATAMA KOTA PEKANBARU) - Elfina, Rini; Siregar, Budi Alamsyah; Suma, Dewi; Alhempi, R Rudi; Putri, Rumanintya Lisaria (Jurnal Apresiasi Ekonomi, 2022)
The era of globalization where every company must compete to maintain and develop its existence, including PT Salim Ivomas Pratama. The main activities of PT Salim Ivomas Pratama start from research, seeding, processing to marketing, the complexity of all activities at PT Salim Ivomas Pratama must be supported by qualified employees and good human resource management. . One of the important elements to improve employee performance is motivation and work discipline. While  the reward and punishment  system plays a role in maintaining the motivation of high-performing employees. The study aims to determine the effect of work motivation and work discipline on employee performance with reward and punishment as mediation variables. Quantitative research using SEM-PLS analysis with the help of SmartPLS application version 3.0. The research instrument was in the form of a questionnaire with a total of 132 respondents. The results of the study found that reward and punishment variables  mediate work motivation variables on employee performance by providing a positive and significant influence shown through calculated values of 2.441< 1,979 tables and p-values of   0.015  < 0.05. Furthermore, reward and punishment can mediate between the variability of work discipline on employee performance positively  and significantly indicated by a calculated value of 4.323< 1,979 ttable and p-value  0.000< 0.05Keyword: Work Motivation, Work Discipline, Employee Performance and Reward And Punishment